Pengaruh Proses Rekrutmen, Seleksi dan Pengembangan Karir Terhadap Kinerja Karyawan pada PT Shou Fong Lastindo di Bojonegoro (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the influence of recruitment, selection, and career development on employee performance at PT Shou Fong Lastindo in Bojonegoro. The study used a quantitative approach with a survey method. The research sample consisted of 85 employees selected using probability sampling techniques. Data were collected through a Likert-scale questionnaire distributed online and analyzed using multiple linear regression with the help of IBM SPSS Statistics. Before testing the hypothesis, the instrument was tested through validity and reliability tests to ensure the quality of the research data. The results showed that partially the selection variable had a positive and significant effect on employee performance (sig. 0.010 < 0.05), while recruitment and career development had no significant effect. Simultaneously, recruitment, selection, and career development had a positive and significant effect on employee performance (sig. 0.000 < 0.05). These findings indicate that the quality of the selection process is the most determining factor in improving employee performance, while the effectiveness of recruitment and career development needs to be optimized to provide a more tangible contribution. This study implies that companies need to implement integrated human resource management to support improved organizational performance and competitiveness.